Finite Mathematics with Business Applications (Book). - Goldberg, Samuel (The Accounting Review, 1963)
Reviews the book "Finite Mathematics with Business Applications," by John G. Kemeny, Arthur Schleifer, J. Laurie Snell and Gerald L. Thompson.